Hubungan Sosio-Demografi dengan Tingkat Pengetahuan Masyarakat Kota Tegal tentang COVID-19: Socio-Demographic Relationship with the Level of Knowledge of the People of the City of Tegal about COVID-19 - Agus Susanto; Ratih Sakti Prastiwi; Kristy Natalia Suwito; Ulfatul Latifah (Jurnal Sains dan Kesehatan, 2021)
COVID-19 has developed into a pandemic and the transmission chart of this new type of disease has ups and downs from day today. The duration of handling COVID-19 is related to the public's level of awareness and knowledge about COVID-19 and its prevention procedures. The level of public awareness and knowledge cannot be separated from socio-demographic factors. This study aims to analyze whether there is a relationship between socio-demography and the level of public knowledge about COVID-19. This study is a cross-sectional study, with a total sample size of 313. The subjects of this study were the people of Tegal City with a minimum age of 18 years. Data analysis used univariate and bivariate analysis. The results showed that most of the respondents' knowledge level was at a sufficient level (71.25%). This study also shows that there is no relationship between gender and age with the level of knowledge (p-value 0.184 & 0.147), while between education and work and the level of knowledge (p-value 0.000 & 0.009). The level of public knowledge is still at the intermediate level, so health promotion activities are needed to raise awareness about COVID-19.